1996
DOI: 10.1093/infdis/174.3.631
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Strain Colonization and Metronidazole Resistance in Helicobacter pylori-Infected Patients: Identification from Sequential and Multiple Biopsy Specimens

Abstract: Helicobacter pylori strain diversity was investigated in infected persons by collection of multiple biopsies before and after therapy failure. It was demonstrated by random amplification of polymorphic DNA polymerase chain reaction that patients may be infected with a mixed population of H. pylori strains. Most patients were colonized with a predominant strain accompanied by up to 5 variant strains. The use of antimicrobials resulted in an altered distribution of the strains present, but the predominant strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
95
2
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(109 citation statements)
references
References 13 publications
11
95
2
1
Order By: Relevance
“…Infections with multiple H. pylori strains have been reported by many authors (16,21,23,35,38). Mixed infection was detected in 7.7% patients and was not related to age and disease.…”
Section: Discussionmentioning
confidence: 83%
“…Infections with multiple H. pylori strains have been reported by many authors (16,21,23,35,38). Mixed infection was detected in 7.7% patients and was not related to age and disease.…”
Section: Discussionmentioning
confidence: 83%
“…H. pylori strains may be diverse in infected patients. Previous studies showed that most patients were colonized with a mixed population of metronidazole-sensitive and -resistant H. pylori strains, and with one predominant strain accompanied by up to five variant strains at any one time (24). Metronidazole-based therapy may selectively enrich for meronidazole-resistant strains.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is emerging that cagA ϩ and cagA Ϫ organisms have differing life-styles in the hosts they colonize and in associations with disease (8). Increasing the complexity of mechanistic analysis are the observations that individuals may be simultaneously colonized by multiple H. pylori strains (29), that strains may change (clonal variation or "quasispecies" formation) over the course of colonization, and that horizontal gene transfer occurs among strains (30). Thus, no single isolate represents the gene pool of the total population with which a host has been colonized.…”
Section: The Modelmentioning
confidence: 99%